Genome Sequence and Comparative Genomics Analysis of a Vibrio cholerae O1 Strain Isolated from a Cholera Patient in Malaysia - Osama, Abdulrazak; Gan, Han Ming; Teh, Cindy Shuan Ju; Yap, Kien Pong; Thong, Kwai Lin (American Society for Microbiology, 2012)
The genome sequence analysis of a clinical Vibrio cholerae VC35 strain from an outbreak case in Malaysia indicates multiple genes involved in host adaptation and a novel Na+-driven multidrug efflux pump-coding gene in the genome of Vibrio cholerae with the highest similarity to VMA_001754 of Vibrio mimicus VMA223.